The effect of labor mobility on corporate investment and performance over the business cycle - Bai, John (Jianqiu); Eldemire, Ashleigh; Serfling, Matthew (Journal of Banking & Finance, 2024)
We show that time-series variation in investment opportunities and labor demand create heterogeneity in the effects of labor mobility on corporate investment over the business cycle. To isolate variation in labor mobility, we create an annual state-level index from 1984 through 2017 that captures the degree to which state courts enforce covenants not to compete. We find that firms located in more mobile labor markets increase investment rates more during economic expansions but have similar investment rates during periods of low or negative growth. This increased investment during expansions is greater for firms that rely more on recruiting skilled and experienced workers to grow their businesses, and it translates into higher sales growth rates, profits, and valuations. Overall, our results suggest that the benefits of being able to recruit qualified workers with relevant experience during expansions outweigh the costs associated with losing key workers.